Equity return volatility in Africa's stock markets: A dynamic panel approach - Godfred Aawaar; Louis Logogye; Daniel Domeher (Cogent Economics & Finance, 2023)
This study examines the determinants of time-varying return volatility of Africa's equity markets using monthly indices of eight top African stock markets. The conditional variance is modelled as a proxy for Africa's volatility indices using the best fitting model among SGARCH, EGARCH and GJR-GARCH. In a bid to account for the dynamic and persistent nature of volatility, the least squares dummy variable bias correction (LSDVC) model is employed. The study finds that volatility of African stock markets follows a dynamic process and is explained by past volatility, domestic exchange rates, Treasury bill rates, money supply, inflation rates, movements in world crude oil prices, volatility of the US and UK stock markets and COVID-19 shocks. The results are largely robust to sub-sample analysis. Further analysis: pre-, during and post-crisis periods (Global Financial Crisis (GFC) and COVID-19 pandemic) reveal that (1) African stock markets became sensitive to advanced market volatility in the period during the GFC and have remained sensitive in the post GFC period and (2) past domestic market return volatility, Treasury bill rates and exchange rates have been the main drivers of stock return volatility during the COVID-19 pandemic in Africa. Additionally, markets in North Africa are revealed as the only African markets immune to advanced market volatility spillovers. These markets may thus provide international diversification opportunities for portfolio managers.
Keywords: C32; F31; G11; G15; 330; African stock markets; Covid-19 Pandemic; GARCH; Global Financial Crisis; LSDVC; volatility